Perancangan Sistem Kompensasi Berbasis Job Value pada RM Terapung Minahasa Utara - Gultom, Shekinah Michelle; Rahmawati, Siti (JUDICIOUS, 2023)
RM Terapung Minahasa Utara is one of the business entities in the food and beverage industry located in North Minahasa Regency. However in practice, RM Terapung Minahasa Utara has not paid salary in accordance with the applicable minimum wage. The purpose of this study was to identify the compensation system implemented by the restaurant, analyze the basic factors for determining compensation (compensable factors), and design an ideal compensation system to be implemented in RM Terapung Minahasa Utara. This research was conducted in February 2023-April 2023. The methods used in this research are descriptive analysis, point method, job value, job grading, salary mapping, adhered and overlapping methods. RM Teapung Minahasa Utara compensation system was not ideal. The compensation factors used in RM Terapung Minahasa Utara are working experience, skill, teamwork, communicating and influencing, customer service orientation, problem solving, physical efforts, working complexity, and responsibility. The ideal compensation system to be implemented by restaurant is an adhered compensation system which located in the min–mid point range.